PHARMACEUTICAL CARE PRACTICE IN THE COMMUNITY PHARMACY BY UTILIZING PROBLEM-BASED LEARNING IN REFLECTIVE PEDAGOGY PARADIGM METHOD - Titien Siwi Hartayu; Yosef Wijoyo; Maria Wisnu Donowati (Sanata Dharma University, 2021)
This study follows the previous study entitle Problem-based Learning (PBL) in reflective pedagogy paradigm (RPP): Innovative learning in pharmaceutical care, which identified the learning material as complicated. This study aimed to provide an appropriate method for performing pharmacy management and pharmaceutical care in Community Pharmacy. Data collection was done using an assessment instrument to identify student’s achievement. The previous study encompasses preceptors and students in developing learning material, which cause it more valid and reliable to be implemented. The study was conducted in Yogyakarta, Surakarta, and Semarang city. The effectiveness of the learning material was shown by the grade of student’s achievement in learning outcome and the clear state with confidence in the expression of reflection and action-plan. Most of the students in the 3 cities achieved an excellent grade both in the problem-solving field, and presentation of the assignment. The students reflected that the learning material is simple and suitable in practicing pharmaceutical care and pharmacy management, moreover, they can state their plan to work as a Community Pharmacist with confidence. Therefore, PBL in the RPP method is ready to be used in practicing pharmaceutical care in the Community Pharmacy.